Energy exchanges in Saturn's polar regions from Cassini observations: Eddy-zonal flow interactions - Read, PL; Antunano, A; Cabanes, S; Colyer, G; Gaztelurrutia, TDR; Sanchez-Lavega, A (Wiley, 2022)
Saturn's polar regions (polewards of ∼63° planetocentric latitude) are strongly dynamically active with zonal jets, polar cyclones and the intriguing north polar hexagon (NPH) wave. Here we analyze measurements of horizontal winds, previously obtained from Cassini images by Antuñano et al. (2015), https://doi.org/10.1002/2014je004709, to determine the spatial and spectral exchanges of kinetic energy (KE) between zonal mean zonal jets and nonaxisymmetric eddies in Saturn's polar regions. Eddies of most resolved scales generally feed KE into the eastward and westward zonal mean jets at rates between 4.3 × 10−5 and 1.4 × 10−4 W kg−1. In particular, the north polar jet (at 76°N) was being energized at a rate of ∼10−4 W kg−1, dominated by the contribution due to the zonal wavenumber m = 6 NPH wave itself. This implies that the hexagon was not being driven at this time through a barotropic instability of the north polar jet, but may suggest a significant role for baroclinic instabilities, convection or other internal energy sources for this feature. The south polar zonal mean jet KE was also being sustained by eddies in that latitude band across a wide range of m. In contrast, results indicate that the north polar vortex may have been weakly barotropically unstable at this time with eddies of low m gaining KE at the expense of the axisymmetric cyclone. However, the southern axisymmetric polar cyclone was gaining KE from non-axisymmetric components at this time, including m = 2 and its harmonics, as the elliptical distortion of the vortex may have been decaying.